The Status of Marine Megafauna Research in Macaronesia: A Systematic Review - McIvor, Ashlie J.; Williams, Collin T.; Alves, Filipe; Dinis, Ana; Pais, Miguel P.; Canning-Clode, João (Frontiers in Marine Science, 2022)
Marine megafauna serve valuable ecological and economical roles globally, yet, many species have experienced precipitous population declines. The significance of marine megafauna is particularly evident in Macaronesia, a complex of oceanic archipelagos in the Northeast Atlantic Ocean. Macaronesian islands provide important habitats for marine megafauna species, in turn supporting considerable regional economic activity (e.g., ecotourism and fisheries). Despite this, concerted efforts to manage marine megafauna throughout Macaronesia have been limited. This systematic review provides the first description of the trends in marine megafauna research in this unique insular ecosystem, to provide a better understanding of taxa-specific research needs and future directions for conservation. We identified and validated 408 peer-reviewed publications until 2021 following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) criteria. Literature was dominated by marine mammal research conducted in the northern archipelagos (Azores, Madeira, and Canary Islands) and marine turtle research conducted in Cabo Verde. Much less research focused on large-bodied fish, especially in Madeira and Canary Islands, leaving some of the most vulnerable species regionally data deficient. Research across scientific disciplines focused more on biological studies than management and policy, and anthropogenic impacts were quantified more frequently on mammals or turtles and less on fishes. By identifying gaps in our knowledge of megafauna in relation to threats faced by these organisms, we offer taxa-specific recommendations for future research direction. Although, overall our results indicate that determining population level connectivity should be a major research priority among many marine megafauna species as this information is vital to numerous management strategies, including marine protected areas. In this review, we present a basis of understanding of the current work in Macaronesia, highlighting critical data gaps that are urgently needed to guide the next steps toward establishing conservation priorities for marine megafauna in the region.